RANCANG BANGUN WEBSITE COMPANY PROFILE DI MAJALENGKA CREATIVE CENTER SEBAGAI IDENTITAS EKONOMI KREATIF - Alam, Muhammad Quthbul; Bastian, Ade (Universitas Majalengka, 2025)
The rapid development of information technology has increased the need for digital media that can effectively represent the identity and activities of institutions. Majalengka Creative Center (MCC), as a hub for creative economy development in Majalengka Regency, requires a digital platform to present its profile, potential, and programs. This study aims to design and develop a company profile website as a digital identity of MCC. The development method applied is Rapid Application Development (RAD), consisting of requirements planning, design, development, and implementation stages. The main technologies used include Next.js as the frontend framework, React.js for user interface components, Tailwind CSS for styling, and Vercel for hosting and deployment. The result is a static website that provides comprehensive information about MCC’s profile, organizational structure, creative economy potential, thematic villages, building facilities, and contact information. The implementation of this website strengthens MCC’s identity, improves public access to information, and supports the promotion of creative economy potential in Majalengka. In the future, the system can be further enhanced by integrating a dynamic database, admin login features, and content management functions to make it more interactive and adaptive to user needs.